Caught Between Theology and History The Integration of Spring Hill College - Stevens, Krista (American catholic studies, 2018)
In 1954, Spring Hill College, a small, Jesuit-run college in Mobile, Alabama, quietly opened its doors to black students. Spring Hill's admission of black students reflected little of the violence and backlash that made national news as other schools across the South integrated over the next fifteen years. Spring Hill's ability to break its own color barrier without public scrutiny was the result of the Jesuit leadership's decision not to mention publicly the school's integration. Thus this decision protected the school, but it also kept a very important historical and theological narrative largely out of the eye of U.S. Catholic history. Spring Hill's story, however, marked an important historical and theological turning point for the Catholic Church in the South in regard to race relations. In 1954, Spring Hill found itself in a unique place in time as the Catholic Church grappled with its identity in an increasing complex and interconnected world. Drawing on historical and theological movements of the early-to-mid twentieth century, Spring Hill's decision to integrate also foreshadowed significant theological movements that would emerge with the Second Vatican Council in the second half of the twentieth century.